Mammal-vehicle collisions on toll roads in São Paulo State: implications for wildlife, human safety and costs for society - Abra, Fernanda Delborgo (2019)
Roads can affect animal movement, dispersal and population aspects (i.e., increasing non-natural mortality) of wild species. Direct road mortality and the barrier effect of roads are typically identified as one of the greatest threats to wildlife. In addition, collisions with large mammals are also a threat to human safety and represent an economic cost to society. Road ecologists worldwide, have used available georeferenced locations of wildlife-vehicle collisions to determine spatial distribution patterns along and the outcomes demonstrates that wildlife-vehicle collisions are not at random, but they are spatially clustered for vertebrate species. Researcher also have used new modelling tools, such as the Species Distribution Modelling (SDM), to orient decision processes on biological conservation as predictive roadkill models (RPM) to determine variables (e.g. landscape, road design, road traffic), that could explain the collisions of specific species. I analyzed roadkill data from toll road companies in São Paulo state during 2005 to 2014. In Chapter 1, I investigated whether maintenance personnel from toll roads companies correctly identified the species of the roadkilled wild mammals on these roads. In Chapter 2, I estimated the roadkill numbers of wild medium and large sized mammals for paved roads (~6,500 km) in São Paulo, based on roadkill data from toll road companies. In Chapter 3, I used SDM approach to generate RPM for eight mammal species on all paved roads in São Paulo state, and I ran roadkill hotspot analysis to identify critical road sections for specific species or animal groups. In Chapter 4, I explored, for the first time in Brazil, the effects of animal-vehicle crashes on human safety on paved roads in São Paulo State, and I estimated the costs of these animal-vehicle crashes to society, and summarized the legal perspectives with regard to liability and associated financial compensation for animal-vehicle collisions. The chapters were specifically planned and designed to understand, in a broad perspective, the different implications related to mammal- vehicle collisions: biological conservation, human safety and economics. The outcomes from each chapter show practical recommendations so that environmental and transportation agencies in São Paulo state can work with planning and priority to reduce mammal-vehicle collisions. This should ultimately result in a road system with improved human safety, reduced unnatural mortality for both domestic and wild animal species, safe crossing opportunities for wildlife, and reduced monetary costs to society.